Transatlantic jurisdictional conflicts in data protection law : fundamental rights, privacy and extraterritoriality / Mistale Taylor. - Taylor, Mistale, 1990- (Cambridge University Press, 2023)
This book looks at transatlantic jurisdictional conflicts in data protection law and how the fundamental right to data protection conditions the EU's exercise of extraterritorial jurisdiction. Governments, companies and individuals are handling ever more digitised personal data, so it is increasingly important to ensure this data is protected. Meanwhile, the Internet is changing how territory and jurisdiction are realised online. The EU promotes personal data protection as a fundamental right. Especially since the EU's General Data Protection Regulation started applying in 2018, its data protection laws have had strong effects beyond its territory. In contrast, similar US information privacy laws are rooted in the marketplace and carry less normative heft. This has provoked clashes with the EU when their values, interests and laws conflict. This research uses three case studies to suggest ways to mitigate transatlantic jurisdictional tensions over data protection and security, the free flow of information and trade.